Embracing an occupational perspective to promoting learning in context - Galvaan, Roshan (South African Journal of Higher Education, 2016)
Traditional occupational therapy practice in schools has been dominated by clinical interventions with children with disabilities or barriers to learning. These practices do not confront many of the challenges facing learners in the dual economy of schooling. This paper advocates that critical occupational therapy, through an Occupation-based Community Development (Ob-CD) approach to practice, is better positioned to address schooling challenges. The value of this approach, in unpacking the transactional nature of occupation for learners attending schools in a low-income area is described. The integrated lens provided by interpreting human occupation in context and framing practice through Ob-CD is highlighted. This is significant for the nature of the relationships formed and the design of interventions within a university- school partnership. A case example illustrates how Ob-CD provides a framework for confronting hegemonic ways of thinking and doing so that fresh perspectives are created for the emergence of new ways of participating. It is advocated that these new pathways provide an impetus for contextually relevant occupational therapy practice while promoting partnerships that foster development.